A Novel CACNA1A Nonsense Variant [c.4054C>T (p.Arg1352⁎)] Causing Episodic Ataxia Type 2 - Sean Lance; Stuart Mossman; Gemma Poke (Case Reports in Neurological Medicine)
Episodic ataxia is a heterogenous group of uncommon neurological disorders characterised by recurrent episodes of vertigo, dysarthria, and ataxia for which a variety of different genetic variations have been implicated. Episodic ataxia type two (EA2) is the most common and also has the largest number of identified causative genetic variants. Treatment with acetazolamide is effective in improving symptoms, so accurate diagnosis is essential. However, a large proportion of patients with EA2 have negative genetic testing. We present a patient with a typical history of EA2 who had a novel variant in the CACNA1A gene not previously described. Report of such variations is important in learning more about the disease and improving diagnostic yield for the patient.